How relationship-maintenance strategies influence athlete burnout: Mediating roles of coach–athlete relationship and basic psychological needs satisfaction - Fan, Fenghui; Chen, Jinyu; Chen, Yunting; Li, Bing; Guo, Liya; Shi, Yang; Yang, Feng; Yang, Qinjun; Yang, Longfei; Ding, Cody; Shi, Huiying (Frontiers in Psychology, 2023)
Introduction Athlete burnout has many potential negative effects on athletes’ sporting performance and careers. Maintaining and promoting the coach–athlete relationship to meet athletes’ basic psychological needs is one way to reduce burnout. Existing studies of the correlation between coach-athlete relationships and athlete burnout have mainly focused on the coaches’ leadership style, with little attention given to relationship-maintenance strategies and the mechanism of athlete burnout from the athletes’ perspective. Methods Using an online survey of 256 adolescent athletes, we explore the relationship between relationship-maintenance strategies and athlete burnout, including the potential mediating effects of the coach–athlete relationship and basic psychological needs satisfaction. Results (1) Athletes’ relationship-maintenance strategies negatively predicted athlete burnout. (2) Besides the direct effect, we found evidence to support three mediation paths: (a) the coach–athlete relationship, (b) basic psychological needs satisfaction, and (c) both as serial mediators. Discussion These findings enhance understanding of the mechanism of athlete burnout, demonstrating the influence of factors beyond the coach’s role. The study also provides a theoretical basis for practical intervention by coaches, athletes, and sports organizations to reduce athlete burnout by focusing on athletes’ perspectives.